Using 7 cm immobilized pH gradient strips to determine levels of clinically relevant proteins in wheat grain extracts - Fekecsová, Sona; Danchenko, Maksym; Uvackova, Lubica; Skultety, Ludovit; Hajduch, Martin (Frontiers in Plant Science, 2015)
The aim of the work was to test relatively simple proteomics approach based on phenol extraction, two-dimensional electrophoresis (2-DE) in combination with 7cm immobilized pH gradient strips for the determination of clinically relevant proteins in wheat grain. Using this approach, 157 2-DE spots were quantified in biological triplicate, out of which 53 were identified by MALDI-TOF/TOF mass spectrometry. Clinically relevant proteins associated with celiac disease, wheat dependent exercise induced anaphylaxis, baker´s asthma, and food allergy, were detected in 24 2-DE spots. The comparison with recent quantitative study suggested that gel-based and gel-free proteomics approaches are complementary for the detection and quantification of clinically relevant proteins in wheat grain.